2015
DOI: 10.1021/acschembio.5b00502
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei Capsular Polysaccharide Recognition by a Monoclonal Antibody Reveals Key Details toward a Biodefense Vaccine and Diagnostics against Melioidosis

Abstract: Burkholderia pseudomallei is the bacterium responsible for melioidosis, an infectious disease with high mortality rates. Since melioidosis is a significant public health concern in endemic regions and the organism is currently classified as a potential biothreat agent, the development of effective vaccines and rapid diagnostics is a priority. The capsular polysaccharide (CPS) expressed by B. pseudomallei is a highly conserved virulence factor and a protective antigen. Because of this, CPS is considered an attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 50 publications
(84 reference statements)
2
32
0
Order By: Relevance
“…Cross reactivity with purified CPSI suggested that the acidic exopolysaccharide-specific antibody reacts with a constituent of CPSI (Fig 7A). We also confirmed that the polysaccharide preparations produced by the becA-R biosynthetic cluster were not CPSI (Fig 7B), since the purified CPSI [14] and preparations from Δ becA-R are reactive to the CPSI-specific 4C4 IgG1 antibody [46, 60, 61], whereas the preparations from Δ wcbR-A mutant and the Δ wcbR-A Δ becA-R double mutants are not reactive to the CPSI-specific 4C4 IgG1 antibody.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Cross reactivity with purified CPSI suggested that the acidic exopolysaccharide-specific antibody reacts with a constituent of CPSI (Fig 7A). We also confirmed that the polysaccharide preparations produced by the becA-R biosynthetic cluster were not CPSI (Fig 7B), since the purified CPSI [14] and preparations from Δ becA-R are reactive to the CPSI-specific 4C4 IgG1 antibody [46, 60, 61], whereas the preparations from Δ wcbR-A mutant and the Δ wcbR-A Δ becA-R double mutants are not reactive to the CPSI-specific 4C4 IgG1 antibody.…”
Section: Resultssupporting
confidence: 68%
“…Immunoblots were probed with either 1:2,000 primary B . pseudomallei -specific CPSl (4C4 IgG1) [46] or 1:2,000 acidic exopolysaccharide (mAb 3015) [15] and detected with goat anti-mouse poly HRP secondary (1:50,000) (Pierce). The immunoblots were visualized using a Clarity Western ECL Blotting Substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Additional insights on the implication of bacterial polysaccharide O‐acetylation in mAb recognition emerged from a recent study on Burkholderia pseudomallei . Molecular investigation on a di‐ O ‐acetylated disaccharide/mAb 4C4 system by means of STD‐NMR and tr‐NOESY analysis confirmed that the O ‐acetyl moiety of the capsular polysaccharide was essential for its interaction with the mAb, as suggested from an investigation on the purified antigen . It is of note that the capsular polysaccharides of S. typhi and B. pseudomallei are O ‐acetylated homopolymers, possibly featuring less antigenic diversity than the more complex SF O‐Ags.…”
Section: Resultsmentioning
confidence: 77%
“…Isolation of mAb 4C4 was described previously [17]. Microtiter plates were coated overnight with 100 μL of mAb 4C4 (2.5 μg/mL in PBS) at room temperature.…”
Section: Methodsmentioning
confidence: 99%